A New Conception of War John Boyd, the U.S. Marines, and Maneuver Warfare - Brown, Ian T. (Marine Corps University Press (MCUP), 2018)
In 1989, the Marine Corps formally adopted a theory of conflict called maneuver warfare and described its tenets in a short but revolutionary doctrinal manual simply titled Warfighting. This conflict theory evolved along two paths that wound their way through the landscape of the late Cold War period before coming together in 1989. A New Conception of War traces this story from the post-Vietnam War years to the present. The first path was forged by U.S. Air Force colonel John R. Boyd, whose ideas on warfare were shaped by a military career during the height of the Cold War and his own passion for challenging conventional wisdom in the search for new and useful ideas. The second path was navigated by many thinkers within the Marine Corps during a period of institutional soul-searching after Vietnam, driven by the Corps' imperative to adapt to the exigencies of the day and thus remain a useful contributor to national defense. Drawing on new and previously unpublished material from the major players of this period, including a full transcript of Boyd's "Patterns of Conflict" lecture, A New Conception of War captures a period of remarkable intellectual ferment within the Marine Corps and the development of a unique conceptual framework for warfighting that continues to inspire Marines today.